Development and initial psychometric evaluation of patient-reported outcome questionnaires to evaluate the symptoms and impact of hidradenitis suppurativa. (17th February 2018) - Kimball, Alexa B.; Sundaram, Murali; Banderas, Benjamin; Foley, Catherine; Shields, Alan L.
Abstract: Background: Two patient-reported outcome (PRO) questionnaires, the Hidradenitis Suppurativa Symptom Assessment (HSSA) and Hidradenitis Suppurativa Impact Assessment (HSIA), were developed to measure signs, symptoms and impacts of HS in treatment efficacy studies. Methods: In accordance with FDA guidelines and published best practices, four stages of research were conducted to create the questionnaires: concept elicitation, questionnaire construction, content evaluation and psychometric evaluation. Results: Subjects ( N  = 20) who participated in the concept elicitation stage reported 15 unique HS-related signs and symptoms and 51 impacts. Following this, eight sign and symptom concepts and 21 impacts were selected for construction of the HSSA and HSIA, respectively. During content evaluation, cognitive debriefing interviews with HS subjects ( N  = 20) confirmed subjects could read, comprehend and meaningfully respond to both questionnaires. Modifications made after this stage of work resulted in a nine-item HSSA and a 17-item HSIA. The HSSA and HSIA were subsequently entered into a US-based observational study ( N  = 40), and the scores produced by each were found to be reliable, construct valid, and able to distinguish among clinically distinct groups. Conclusions: The HSSA and HSIA are content-valid, HS-specific, PRO questionnaires with demonstrated ability to generate reliable, valid scores when administered to patients with HS in a research setting.